Video theories a transdisciplinary reader - Daniels, Dieter 1957-; Thoben, Jan 1978- (Bloomsbury Academic, 2022)
Preface / Dieter Daniels and Jan Thoben -- Formations : exemplary discourses -- Medium specificity and hybridity : the materiality of the electronic image -- Video and the self : closed circuit : feedback : narcissism -- Video : film -- Video : television -- Video : sound and synthesis -- Video : performance and theater -- Video : internet : online video and the consumer as producer -- Sociality : participation : utopias -- Communities : amateurism : ethnographies : participation -- Surveillance : exposure : testimony : forensics -- Artistic practice and video theory
Includes bibliographical references and index
Keywords: Medientheorie; Videokunst; Video; Video recordings; Digital video; Video art; Aufsatzsammlung